Analysis of the Impact of Digital Marketing Strategy on the Growth of Startup Businesses in Indonesia - Ridwan Ridwan; Ekaterina Ivanova (Greenation International Journal of Economics and Accounting, 2024)
This study investigates the impact of digital marketing strategies on the growth of startup businesses in Indonesia, utilizing a mixed-method approach combining both qualitative and quantitative data. Qualitative data were collected through in-depth interviews and case studies, while quantitative data were gathered through surveys from 150 startups across various sectors. The results show that Search Engine Optimization (SEO) is the most effective strategy, with a 72% correlation to revenue growth and a 68% correlation to customer acquisition. Social media marketing had a 60% correlation with revenue growth and a 55% correlation with customer acquisition, indicating its positive, though slightly weaker, impact compared to SEO. Paid advertising showed a 58% correlation with revenue growth and a 60% correlation with customer acquisition, suggesting it plays a role, but with a lower impact than SEO and social media marketing. A multiple regression analysis confirmed that all three strategies—SEO, social media, and paid advertising—significantly predict revenue growth, with SEO being the strongest predictor (? = 0.35, p < 0.01). The study emphasizes that startups employing a combination of these digital marketing strategies experienced higher overall growth, suggesting that an integrated approach is key to maximizing business success. These findings provide valuable insights for startup owners and marketers to optimize their strategies in a competitive digital landscape.